Eucomis nubigena (Hyacinthaceae, Hyacinthoideae), a diminutive new cleistogamous species from the Drakensberg Mountain Centre - Crouch, Neil R.; Martínez-Azorín, Mario; Cron, Glynis V.; Beaumont, Angela J. (Phytotaxa, 2025)
Based on morphological and ecological grounds, and its reproductive strategy, Eucomis nubigena is here described. This is a diminutive new dwarf species found at high elevations in both South Africa and Lesotho, limited in distribution to the Maloti Alpine Sub-centre of the Drakensberg Mountain Centre. This cryptic geophyte is restricted to basaltic substrates, growing in full sun in shallow pockets of gravel overlying basalt pavements. It is easily differentiated from its closest relatives based on its overall diminutive size, the production of flowers that are exclusively cleistogamous and autogamous rather than chasmogamous and entomophilous, and its prominently succulent coma bracts. Eucomis nubigena is the first species in a widely distributed family of ca. 1000 species to be documented as cleistogamous, and the first genus member to exhibit basal placentation. A complete illustration and morphological description of the new species are provided, including data regarding its biology, ecology, and distribution. The relationship of E. nubigena to other genus members is assessed.